New Molecules and Old Drugs as Emerging Approaches to Selectively Target Human Glioblastoma Cancer Stem Cells. (2nd January 2014) - Würth, Roberto; Barbieri, Federica; Florio, Tullio
Abstract : Despite relevant progress obtained by multimodal treatment, glioblastoma (GBM), the most aggressive primary brain tumor, is still incurable. The most encouraging advancement of GBM drug research derives from the identification of cancer stem cells (CSCs), since these cells appear to represent the determinants of resistance to current standard therapies. The goal of most ongoing studies is to identify drugs able to affect CSCs biology, either inducing selective toxicity or differentiating this tumor cell population into nontumorigenic cells. Moreover, the therapeutic approach for GBM could be improved interfering with chemo- or radioresistance mechanisms, microenvironment signals, and the neoangiogenic process. During the last years, molecular targeted compounds such as sorafenib and old drugs, like metformin, displayed interesting efficacy in preclinical studies towards several tumors, including GBM, preferentially affecting CSC viability. In this review, the latest experimental results, controversies, and prospective application concerning these promising anticancer drugs will be discussed.